Study on pyrolysis behavior and kinetics of waste plastics with spent FCC catalyst. Issue 2 (15th November 2022) - Shan, Tilun; Wang, Kongshuo; Bian, Huiguang; Fan, Fangshuo; Xiao, Yao; Pan, Yi; Tian, Xiaolong; Wang, Chuansheng
Abstract: Pyrolysis is the most promising method for treating plastic waste since it can convert waste plastics into high value‐added products, which have significant application potential. In this study, kinetic and thermodynamic analyses of spent fluid catalytic cracking (FCC) catalysts were performed for testing their applicability in catalytic cracking of mixed plastics. Thermogravimetric analysis data were obtained at different heating rates under an inert atmosphere, and the synergistic effect between the mixed plastics and activation energy reduction before and after pretreatment of the spent FCC catalysts was discussed. Through a variety of model‐free methods (Flynn‐Wall‐Ozawa, Kissinger‐Akahira‐Sunose, Starink, and Kissinger methods), it is proved that the spent FCC catalyst facilitates the reduction in activation energy required for the pyrolysis of plastics, which is reduced by approximately 13% from 278 to 242 kJ/mol. The catalytic performance of spent FCC catalyst was improved after pretreatment, while its activation energy decreased by approximately 21% from 278 to 220 kJ/mol. The Friedman‐Reich‐Levi method was used to fit the curve, and the number of mechanism functions in plastic pyrolysis was determined according to the slope of the fitting curve. The C‐R method was used in combination with the Malek method to determine the optimal mechanism function. Moreover, kinetic parameters of the spent FCC catalyst for catalytic cracking of plastics were obtained via kinetic studies on the pyrolysis of mixed plastics, which provided theoretical guidance for industrialization of plastic pyrolysis.